Factors Contributing to Learners’ Autonomy in EFL Reading - Sri Endah Tabiati (Pascasarjana UM, 2016)
Abstract: This study aims to discover factors that assist learners develop their autonomy in EFL reading. The approach employed is qualitative involving EFL learners in an English Department of the Faculty of Cultural Studies, Brawijaya University Malang. There are two stages in the study: the subject selection stage intended to gain potential subjects and the main study intended to find the answer of the research questions. The findings of the study show that the autonomy of EFL learners in reading is influenced by 14 internal and 14 external factors.These factors appear to happen naturally. It seemed that autonomy in reading is subconscious and has been gained by the subjects gradually since childhood. Moreover, autonomy in EFL reading is presumed to be universal as it is found in a collectivist culture such as the one in Indonesia. Based on the findings, suggestions are proposed and addressed to Reading lecturers, parents and the faculty representing the goverment. Because the factors seem to occur before they study at a university, the suggestions are also addressed to teachers and schools. Key Words: internal factors, external factors, contribution, learners’ autonomy, EFL readingAbstrak: Penelitian ini bertujuan untuk menemukan faktor yang membantu mahasiswa dalam mengembangkan kemampuannya secara otonom pada kemampuan membaca EFL. Penelitian ini menggunakan desain kualitative dengan melibatkan mahasiswa kategori EFL Fakultas Ilmu Budaya Universitas Brawijaya Malang. Terdapat dua thapa dalam penelitian ini. Tahap pertama merupakan pemilihan subyek yang bertujuan untuk mencari subyek yang berpotensi dan setelah itu penelitian dilakukan untuk menjawab rumusan masalah. Hasil penelitian ini menunjukan bahwa sikap otonom mahasiswa EFL dalam kemampuan membaca dipengaruhi oleh 14 faktor internal dan 14 faktor eksternal. Faktor-faktor tersebut muncul secara natural. Terlihat bahwa sikap otonom dalam kemampuan membaca merupakah hal yang terjadi diluar kesadaran dan didapatkan secara bertahap sejak dini. Terlebih lagi, sikap otonom dalam kemampuan membaca EFL diduga merupakan nilai universal sebagaimana terlihat pada budaya kolektivis masyarakat Indonesia. Maka dari itu, beberapa saran yang dapat diberikan kepada Dosen pengajar Kemampuan Membaca, orang tua, dan anggota fakultas. Karena faktor tersebut muncul sebelum kegiatan perkuliahan di Universitas, maka beberapa saran juga ditujukan kpeda guru dan sekolah. Kata kunci: faktor internal, faktor eksternal, kontribusi, sikap otonom, EFL, kemampuan membaca